Anti-Inflammatory Potentials of β-Ketoester Derivatives of N-Ary Succinimides: In Vitro, In Vivo, and Molecular Docking Studies. (7th July 2022) - Alqahtani, Yahya S.; Jan, Muhammad Saeed; Mahnashi, Mater H.; Alyami, Bandar A.; Alqarni, Ali O.; Rashid, Umer; Mahmood, Fawad; Tariq, Muhammad; Sadiq, Abdul
Abstract : Inflammation, being a well-known and complex pathological condition, is always a challenge to the human health. This research work was designed for a rationale-based anti-inflammatory study on β -ketoester derivatives of N-ary succinimides. The compounds (A –D ) were synthesized by organocatalytic Michael addition. The compounds were initially screened for in vitro 5-lipoxygenase (5-LOX) and cyclooxygenase (COX-2) assays. For the in vivo activity, carrageenan-induced paw edema and arachidonic acid-induced ear edema tests were used. Furthermore, different in vivo pathways such as prostaglandins E 2, histamine, leukotriene, and bradykinin were studied. The results were supported with molecular docking studies. Among the compounds, D (ethyl 1-(1-benzyl-2, 5-dioxopyrrolidin-3-yl)-2-oxocyclohexane-1-carboxylate) at a concentration of 1000 μ g/ml showed significant inhibitory effects of 83.67% and 78.12% against COX-2 and 5-LOX in comparison to celecoxib and zileuton, respectively. Similarly, compound D also showed excellent in vivo anti-inflammatory potential. Amongst all the compounds, D demonstrated excellent (55.92 ± 2.95%) anti-inflammatory potential at maximum tested dose (100 mg/kg) which accomplished the highest significance at 4 h following the carrageenan insertion and stayed considerable ( ∗ ∗ ∗ P < 0.001 ) till the 5th hour of test sample injection. Compound D also exhibited excellent percent inhibition (63.81 ± 2.24%) at the highest dose in arachidonic acid-induced ear inflammation. On the basis of in vivo and in vitro results, compound D was subjected to various inflammation-causing agents such as histamine, prostaglandins E 2, bradykinin, and leukotriene via the mouse paw edema test. Compound D revealed moderate effect (28.10 ± 1.64%) against histamine-induced paw edema while nonsignificant result (9.72 ± 3.125%) was marked for the bradykinin pathway. Compound D showed significance against edematogenic consequence of prostaglandin E 2 (56.28–72.03%) and leukotriene (55.13 ± 2.25%) induced inflammation. In summary, our findings recommended that compound D possesses double acting anti-inflammatory properties inhibiting both COX and LOX pathways. Binding orientations and energy values computed via docking simulations support the results of the experimental in vitro evaluation.